Impact of prior exercise on hamstring flexibility: A comparison of proprioceptive neuromuscular facilitation and static stretching - Funk, D. C.; Swank, A. M.; Mikla, B. M.; Fagan, T. A.; Farr, B. K. (The Journal of Strength and Conditioning Research, 2003)
Position stands from the American College of Sports Medicine and the Surgeon General site a need for strategies capable of enhancing the effectiveness of stretching on flexibility and joint range of motion. One strategy for enhancing flexibility that has received anecdotal support but lacks substantial experimental evidence is the impact of prior exercise. This study compared 5 minutes of static stretching and proprioceptive neuromuscular facilitation (PNF) on hamstring flexibility performed with and without exercise. Forty undergraduate student-athletes participated in a repeated measure, counterbalanced experimental design. Within-group comparisons indicated that PNF resulted in a significant (p < 0.05) increase in flexibility after 60 minutes of exercise when compared with baseline (9.6%) and without exercise (7.8%). No differences were observed with static stretching across time. In addition, no differences were observed between the groups at any time point. Results demonstrated that PNF performed after exercise enhanced acute hamstring flexibility, and implementing a PNF stretching routine following exercise may augment current stretching practices among athletes.